2016
DOI: 10.1055/s-0036-1584923
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus: Epidemiology, Global Spread of Novel Serotypes, and Advances in Treatment and Prevention

Abstract: Adenoviruses (AdVs) are DNA viruses that typically cause mild infections involving the upper or lower respiratory tract, gastrointestinal tract, or conjunctiva. Rare manifestations of AdV infections include hemorrhagic cystitis, hepatitis, hemorrhagic colitis, pancreatitis, nephritis, or meningoencephalitis. AdV infections are more common in young children, due to lack of humoral immunity. Epidemics of AdV infection may occur in healthy children or adults in closed or crowded settings (particularly military re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
181
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(185 citation statements)
references
References 318 publications
(756 reference statements)
1
181
0
3
Order By: Relevance
“…The predominant HAdV genotypes detected in association with clinical presentation differ among different countries and may change over time. 16 Currently in Switzerland, the knowledge on the molecular epidemiology and clinical presentation of HAdV infection is lacking. This study presents the molecular epidemiology of HAdV and associated clinical findings based on a retrospective observational study from laboratory confirmed HAdV cases collected between 1998 and 2017, at the Institute for Infectious Disease (IFIK), following referral of specimens by clinicians from the largest hospitals and other regional clinics in Bern.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant HAdV genotypes detected in association with clinical presentation differ among different countries and may change over time. 16 Currently in Switzerland, the knowledge on the molecular epidemiology and clinical presentation of HAdV infection is lacking. This study presents the molecular epidemiology of HAdV and associated clinical findings based on a retrospective observational study from laboratory confirmed HAdV cases collected between 1998 and 2017, at the Institute for Infectious Disease (IFIK), following referral of specimens by clinicians from the largest hospitals and other regional clinics in Bern.…”
Section: Introductionmentioning
confidence: 99%
“…Human adenoviruses (HAdV)belong to the genus Mastadenovirus of family Adenoviridae and consist of 7 species (HAdV-A through HAdV-G) including over 70 serotypes [2]. While different genotypes may cause different clinical features.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis and treatment of Adv infection was performed according the State Administration of National Health Commission of the People's Republic of China and national guidelines published in 2019 (19). All children received standard treatment for pneumonia, which included supportive care when necessary, invasive or non-invasive ventilation, and antibiotics.…”
Section: Treatment Modalitiesmentioning
confidence: 99%